1985
DOI: 10.1111/j.1365-2621.1985.tb13019.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fatty Acid Composition of Papaya Lipids (Carica papaya) During Ripening

Abstract: Lipids from papayas (Curica papaya L.) Solo cultivar at various stages of ripeness were extracted and fractionated into neutral lipids (NL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Polar lipids are known to be an important constituent of membrane lipids (15). These results agreed with the previous observations on mango {12}, papaya (20) and Concord grape (V iris labrusca var. Erucic acid of rapeseed {16-18} and petroselinic acid of parsley seed (19) were localized on nonpolar lipid fractions.…”
Section: Resultssupporting
confidence: 93%
“…Polar lipids are known to be an important constituent of membrane lipids (15). These results agreed with the previous observations on mango {12}, papaya (20) and Concord grape (V iris labrusca var. Erucic acid of rapeseed {16-18} and petroselinic acid of parsley seed (19) were localized on nonpolar lipid fractions.…”
Section: Resultssupporting
confidence: 93%
“…OECD (2010) indicated that FA levels are low in papaya and palmitic acid and linolenic acid are the two major FAs in papaya. Chan and Taniguchi (1985) reported that FA composition changes in papaya pulp during fruit ripening stage, however, no significant difference was found in lipid composition with maturity of papaya fruits.…”
Section: Introductionmentioning
confidence: 93%